EFFORTS TO PROTECT CONSUMER’S SPIRITUAL RIGHTS IN ORGANIZING ISLAMIC MICROFINANCE INSTITUTIONS IN INDONESIA - Hari Sutra Disemadi; Ayup Suran Ningsih (Diponegoro Law Review, 2020)
Microfinance Institutions (MFIs) are part of non-bank financial institutions. In organizing, MFIs can be implemented with sharia principles, but not a few people who assume that this Sharia-based MFI is only a label to attract the sympathy of the Muslim community. Based on this, this study aims to determine the legal policies for the implementation of MFIs in Indonesia and to find out regulatory policies regarding sharia principles in the organization of MFIs as an effort to protect the spiritual rights of consumers. This study uses a normative juridical research method with a conceptual approach and a statutory approach. This study shows the legal basis for the organization of MFIs is Law Number 1 of 2013, POJK Number 14/POJK.05/2014, POJK Number 61/POJK.05/2015, and POJK Number 62/POJK.05/2015. The policy of regulating the application of sharia principles as an effort to protect the spiritual rights of consumers has also been regulated in the MFI Law and the implementing regulations namely POJK Number 62/POJK.05/2015 concerning Business Administration of MFIs which in the implementation of sharia-based MFIs must use mudharabah, musyarakah, murabahah, ijarah, salam, istishna, ijarah muntahiah bit tamlik or other contracts (akad) that do not conflict with sharia principles. The policy of applying sharia principles in organizing MFIs is intended to guarantee the protection of the spiritual rights of consumers from Islamic MFIs.